Konsep Diri, Kecerdasan Emosi dan Motivasi Belajar Siswa - Asy'ari, M; Ekayati, IGAA Novi; Matulessy, Andik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract.Â The purpose of this study was to determine the relationship between self-concept and emotional intelligence with student motivation. The sample was SMK Assaâ€™adah Sampurnan Bungah Gresik amount to 167 students by using random sampling techniques Purpose. The result of multiple regression analysis obtained Fhitung by 62,551 with Ï < 0.05 is Ï = 0,000, which means there is a significant relationship between self-concept and emotional intelligence with student motivation; itâ€™s means there is very significant relationship between self-concept and student motivation with t = 3,178 and Ï = 0,000, and very significant relationship between emotional intelligence and student motivation with t = 5,286 and Ï = 0,000. The percentage contribution of effective self-concept and emotional intelligence for student motivation is equal 73,3%.Key Words : self-concept, emotional intelligence, and student motivation.